A temperature-programmed reaction/single-photon ionization time-of-flight mass spectrometry system for rapid investigation of gas–solid heterogeneous catalytic reactions under realistic reaction conditions. Issue 11 (7th October 2015) - He, Songbo; Cui, Huapeng; Lai, Yulong; Sun, Chenglin; Luo, Sha; Li, Haiyang; Seshan, K.
Abstract : A new TPRn/SPI-TOF-MS system for rapid investigation of realistic gas–solid heterogeneous catalytic reactions. Abstract : A Temperature-Programmed Reaction (TPRn)/Single-Photon Ionization Time-of-Flight Mass Spectrometry (SPI-TOF-MS) system is described. The TPRn/SPI-TOF-MS system allows rapid characterization of heterogeneous catalytic reactions under realistic reaction conditions and at the same time allows for the description of the reaction schemes.